FIGHTING FOR A BETTER ACHIEVEMENT OF ENGLISH: WHAT SHOULD INDONESIAN EFL STUDENTS DO? - Tono Suwartono (Widya Mandala Surabaya Catholic University, 2018)
This paper is presented through the lens of two-folded perspectives: the author as a teacher and the author as a learner of English. As a teacher of English, the author will put forward some professional viewpoints in relation with the difficulties that Indonesian students face when learning English and with what they should do in coping with the problems. As a learner, the author will share his own experiences and success stories as a good learner of English in the past. As the title of the paper implies, overall, this paper mainly discusses the major constraints that hinder Indonesian students’ EFL learning progress and offers feasible approaches to the challenges to meeting the expectation: a significant success in EFL learning in Indonesia.